Toxoplasma gondii Infection of Neurons Induces Neuronal Cytokine and Chemokine Production, but Gamma Interferon- and Tumor Necrosis Factor-Stimulated Neurons Fail To Inhibit the Invasion and Growth of T. gondii - Schlüter, D. (American Society for Microbiology, 2001)
The intracellular parasite Toxoplasma gondii has the capacity to persist in the brain within neurons. In this study we demonstrated that T. gondii infected murine cerebellar neurons in vitro and replicated within these cells. Stimulation with gamma interferon (IFN-γ) and/or tumor necrosis factor (TNF) did not enable neurons to inhibit parasite invasion and replication. Cultured neurons constitutively produced interleukin 1 (IL-1), IL-6, macrophage inflammatory protein 1α (MIP-1α), and MIP-1β but not transforming growth factor β1 (TGF-β1), IL-10, and granulocyte-macrophage colony-stimulating factor. Neuronal expression of some cytokines (IL-6, TGF-β1) and chemokines (MIP-1β) was regulated by infection and/or by IFN-γ and TNF.